Pragmatic Analysis of Flouting Maxim in Romantic Dialogue: A Case Study of Dilan 1990 - Dery Purnama Saefudin; Prima Pantau Putri Santosa; Ukti Lutvaidah; Restoeningroem Restoeningroem; Suhfi Albab; Adah Puadah (JELITA, 2025)
Dilan 1990 is a popular Indonesian film known for its romantic dialogue and engaging narrative. This study analyzes the use of flirtatious remarks within the film through Grice's Cooperative Principle, focusing specifically on the concept of flouting his four maxims: Quantity, Quality, Relevance, and Manner. The analysis reveals that the maxim of Relevance is most frequently flouted (18 instances, 32%), followed by Quantity (17 instances, 30%), Quality (15 instances, 26%), and Manner (7 instances, 12%). This pattern suggests that the characters prioritize emotional expressiveness and romantic appeal over strict adherence to conversational norms. The flirtatious remarks often manipulate language strategically to heighten romantic tension and evoke humor, which significantly contributes to the film’s charm and cultural resonance. These findings provide valuable insights into the pragmatic strategies of flouting used in romantic discourse and their impact on viewer engagement and narrative effectiveness, highlighting the complexities of youthful romance.